MULTIPLE EXPOSURE PHOTOGRAPHY TECHNIQUES IN TRADITIONAL DANCE MOVEMENTS AS AN ALTERNATIVE TO LEARNING MEDIA - Deddy Award Widya Laksana; Bernardus Andang Prasetya Adiwibawa (JURNAL PAKARENA, 2022)
Learning technology tools need to be designed to make it easier for students to learn effortlessly and achieve optimal results in particular materials and situations. Traditional dance is one of the learning materials that focus on psychomotor aspects through understanding movement. When face-to-face learning processes are not allowed, it is necessary to develop appropriate learning technology devices. The multiple exposure photography technique is feasible as an alternative to the traditional dance learning media. The technique is considered by comparing the criteria for developing learning media. The result achieved is a graphic media about traditional dance movements.